2014
DOI: 10.1038/labinvest.2014.117
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid inhibits experimental colitis by preventing early intestinal epithelial cell death

Abstract: Ulcerative colitis (UC) is characterized by increased epithelial cell death and subsequent breakdown of the intestinal epithelial barrier, which perpetuates chronic intestinal inflammation. Since fecal bile acid dysmetabolism is associated with UC and tauroursodeoxycholic acid (TUDCA) has been shown to improve murine colitis, we evaluated the effect of TUDCA on intestinal epithelial cell death in a mouse model of UC-like barrier dysfunction elicited by dextran sulfate sodium (DSS). We identified the prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 35 publications
4
63
0
Order By: Relevance
“…Previous studies have reported the therapeutic potential of the hydrophilic bile acids UDCA and TUDCA in experimental colitis (11,15,16), albeit without comparing their respective effectiveness. In the present study, we showed that daily administration of UDCA and its taurine-and glycine-coupled conjugates equally attenuated body weight loss, disease activity, and colonic shortening caused by DSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the therapeutic potential of the hydrophilic bile acids UDCA and TUDCA in experimental colitis (11,15,16), albeit without comparing their respective effectiveness. In the present study, we showed that daily administration of UDCA and its taurine-and glycine-coupled conjugates equally attenuated body weight loss, disease activity, and colonic shortening caused by DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that fecal bile acid hydrophobicity correlates with the severity of colitis (14), it is reasonable to assume that conjugates of UDCA, which are more hydrophilic than unconjugated UDCA, might be more favorable therapeutic agents for intestinal inflammation. In this regard, we and others have shown that tauroursodeoxycholic acid (TUDCA) alleviates dextran sodium sulfate (DSS)-induced colitis in mice (15,16). The potential beneficial effect of glycoursodeoxycholic acid (GUDCA) in colitis, however, has not been addressed so far, and studies comparing the therapeutic effectiveness of these different bile acid species are lacking.…”
mentioning
confidence: 99%
“…A previous study showed that TUDCA can reduce cytotoxicity in IECs, whereas UDCA cannot . Moreover, TUDCA has been shown to improve murine colitis . Based on these results, TUDCA would be safer and more efficient than UDCA, indicating TUDCA as a suitable candidate for clinical trials for treating IBD and preventing CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TUDCA has been identified as a chemical chaperone against endoplasmic reticulum (ER) stress in the IECs . In addition, TUDCA attenuates acute and chronic colonic inflammation by reducing ER stress . Although these studies indicate that TUDCA has an anti‐inflammatory effect, little information is available with regard to CAC.…”
Section: Introductionmentioning
confidence: 99%
“…For the past thousand years, UDCA has been isolated from dried black bear gallbladders and used in the treatment of several illnesses in traditional Chinese medicine (Beuers, 2006). Nowadays, TUDCA has been chemically synthesized and is widely used in clinical and experimental research to treat liver disease, diabetes, and neurodegenerative diseases (Momose et al, 1997, Keene et al, 2002, Rodrigues et al, 2003, Green and Kroemer, 2004, Ozcan et al, 2006, Kars et al, 2010, Ceylan-Isik et al, 2011, Laukens et al, 2014). Previous research revealed that TUDCA functioned by modulating the apoptotic threshold in various cell types (Rodrigues et al, 2003, Amaral et al, 2009, Ramalho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%